Suprachoroidal spheroidal mesenchymal stem cell implantation in retinitis pigmentosa: clinical results of 6 months follow-up - ŞAHİN, ÖZLEM (My University, 2023)
Purpose: This prospective clinical case series aimed to evaluate the effect of suprachoroidal implantation of mesenchymal stem cells (MSCs) in the form of spheroids as a stem cell therapy for retinitis pigmentosa (RP) patients with relatively good visual acuity. Methods: Fifteen eyes of 15 patients with RP who received suprachoroidal implantation of MSCs in the form of spheroids were included. Best-corrected visual acuity (BCVA), 10–2 and 30–2 visual field examination and multifocal electroretinography (mfERG) recordings were recorded at baseline, postoperative 1st, 3rd and 6th months during follow-up. Results: Baseline median BCVA of RP patients was 1.30 (1.00–2.00) logMAR. BCVA has improved to 1.00 (0.50–1.30), 0.80 (0.40–1.30) and 0.80 (0.40–1.30) at the postoperative 1st, 3rd and 6th months, respectively. The improvements from baseline to the 3rd and 6th months were statistically significant (p = 0.03 and p < 0.001, respectively). In the 30–2 VF test, median MD was significantly improved at the 6th month compared to baseline (p = 0.030). In the 10–2 VF test, the median MD value was significantly different at the 6th month compared to the baseline (p = 0.043). The PSD value of the 10–2 VF test was significantly different at the 6th month compared to the 3rd month (p = 0.043). The amplitudes of P1 waves in < 2°, 5°–10° and 10°–15° rings improved significantly at the postoperative 6th month (p = 0.014, p = 0.018 and p = 0.017, respectively). There was also a statistically significant improvement in implicit times of P1 waves in 10°–15° ring at the postoperative 6th month (p = 0.004). Conclusion: Suprachoroidal implantation of MSCs in the form of spheroids as a stem cell therapy for RP patients with relatively good visual acuity has an improving effect on BCVA, VF and mfERG recordings during the 6-month follow-up period. Spheroidal MSCs with enhanced effects may be more successful in preventing apoptosis and improving retinal tissue healing in RP patients.
Keywords: Tıp; Histoloji-Embriyoloji; Yaşam Bilimleri; Biyoteknoloji; Moleküler Biyoloji ve Genetik; Sitogenetik; Sağlık Bilimleri; Temel Tıp Bilimleri; Temel Bilimler; Medicine; Histology and Embryology; Life Sciences; Biotechnology; Molecular Biology and Genetics; Cytogenetic; Health Sciences; Fundamental Medical Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Mikrobiyoloji; TIP, GENEL & DAHİLİ; HÜCRE BİYOLOJİSİ; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; BİYOTEKNOLOJİ VE UYGULAMALI MİKROBİYOLOJİ; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; MOLECULAR BIOLOGY & GENETICS; MICROBIOLOGY; MEDICINE, GENERAL & INTERNAL; CELL BIOLOGY; BIOCHEMISTRY & MOLECULAR BIOLOGY; BIOTECHNOLOGY & APPLIED MICROBIOLOGY; Tıp (çeşitli); Moleküler Tıp; Biyokimya, Genetik ve Moleküler Biyoloji (çeşitli); Hücre Biyolojisi; Medicine (miscellaneous); Molecular Medicine; Biochemistry, Genetics and Molecular Biology (miscellaneous); Cell Biology; Mesenchymal stem cells; Retinitis pigmentosa; Spheroids; Suprachoroidal implantation; Retinitis pigmentosa; Mesenchymal stem cells; Spheroids; Suprachoroidal implantation